Synthesis and characterization of orotic acid loaded chitosan inclusion complex - Hassani, Abdelkader; Azad, Abul Kalam; Enezei, Hamid H.; Hussain, Siti A.; Helal Uddin, A.B.M. (International Journal of Drug Delivery Technology, 2020)
The current study aims to improve drug release properties of orotic acid loaded with chitosan inclusion complex (OA/CS). The OA/CS inclusion complex was synthesized using the freeze-drying technique. The characterization of inclusion OA/ CS was carried out using fourier transform infrared spectroscopy (FTIR), X-ray diffractometry (XRD), differential scanning calorimetry (DSC), zeta sizer, and transmission electron microscopy (TEM). Furthermore, the size of OA/CS ranged between 58 nm and 200 nm, and the zeta potential was 30 mV. Thus, this study indicates that OA/CS has a promising future to develop a carrier for drug delivery systems further. Keywords: Chitosan, Drug delivery, Inclusion complex, Orotic acid, Synthesis. International Journal of Drug Delivery Technology (2020); DOI: 10.25258/ijddt.10.1.1 How to cite this article: Hassani A, Azad AK, Enezei HH, Hussain SA, Helal Uddin ABM. Synthesis and Characterization of Orotic Acid Loaded Chitosan Inclusion Complex. International Journal of Drug Delivery Technology. 2020; 10(1): 1-4.